Lack of Staphylococcal Enterotoxin Production among Strains of Staphylococcus aureus from Bovine Mastitis in Denmark - Aarestrup, F. M. (Acta Vet Scand, 1995)
Staphylococcal enterotoxins (SE’s) are a group of small exoproteins produced by some strains of Staphylococcus aureus. The SE’s, designated A to E according to their antigenic specificities, are important causes of food poisoning worldwide. Milk and dairy products are frequently associated with S. aureus enter-otoxin food poisoning, and it is supposed that infected milk from mastitic animals constitute the main source of enterotoxigenic S. aureus of animal origin (Bryon 1983, Gilmour & Harvey 1990, Bergdoll 1989). Indeed, S. aureus is the most common cause of bovine mastitis worldwide, and if mastitis strains produce SE this makes up an enormous reservoir of potential enterotoxin producers. The production of SE by S. aureus isolated from bovine mastitis have been investigated in several countries (Matsunaga et al. 1993, Kenny et al. 1993, Olson et al 1970, Orden et al. 1992, Olsvik et al. 1981, Adekeye 1980, Garcia et al. 1980, Abbar 1986, Harvey & Gilmour 1985). Since no studies have been performed on the prevalence of enterotoxigenic strains of S. aureus isolated from bovine mastitis in Denmark, a well characterized collection of S. aureus (Aarestrup et al. 1995) was investigated with respect to this property.